Syakk dan Roib: Konsep dan Implikasi dalam Al-Qur’an - Fiy, Muhammad Shun Fan'Ulum (Prodi Ilmu al-Qur'an dan Tafsir, 2024)
This research explores the concept of Syakk and Roib in the Qur'an and its implications for people who have syakk and roib in their hearts, especially those who are polytheists because of their ignorance and arrogance. Anxiety will arise for those who experience doubt and loss in their hearts. what the words syakk and roibun look like from the perspective of the Koran, the relationship between syakk and roibun and then comparing the two words and what the implications are for those who have feelings of syakk and roib. We collected verses that say syakk and roib, there are 15 verses that say syakk from 11 different verses while the word roib is only found in one verse. Their doubts relate to the Torah, Bible and Al-Qur'an, doubts about the preaching of His apostles, doubts about the last day and doubts about the divinity of Allah SWT as the creator of the heavens and the earth. Syakk and roib arise from a lack of knowledge, closing oneself and sticking to tradition. Syakk and roib will have the implications of these things appearing in his heart: Having no certainty, being overwhelmed by wrong conjectures and prejudices, having his heart blinded by Allah, being prevented from moving towards the truth, becoming a person who loses and commits disgraceful actions and does not receive guidance.